(untitled) (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2022)
The school is under a coherent and uniform education system but is composed of different leadership lines assisted by teachers who learn teaching using the same system and syllabus according to their respective options. What teachers will go through is working under diverse leadership styles and climates. The transformational leadership style is oriented to the existence of a climate conducive to subordinates. This study aims to identify the level of transformational leadership practice of headmasters, the level of conflict, differences significance of teachers according to gender, age and experience and the relationship between transformational leadership of headmaster and conflict among teachers of Sekolah Kebangsaan di Daerah Kota Setar. The study involved 30 respondents consisting of teachers Sekolah Kebangsaan di Daerah Kota Setar. The study variables were tested using descriptive statistics and inferences involving mean scores, standard deviations, independent sample t-tests, one-way ANOVAs dan Pearson correlation. Data were analyzed using IBM SPSS version 26.0 for windows. The findings show that the transformational leadership of the headmasters (Min = 4.20; SD = .58 ) and the teacher conflict management (Min = 3.60; SD = .46 ) are high. Pearson’s correlation analysis found that ten dimensions of headmasters’ transformational leadership had NO significant relationship with teacher conflict management. Finally, the findings of this study are expected to contribute significantly to the body of knowledge by highlighting the relationships among the variables involved. The findings of this study can also be used by certain parties to realize school excellence.